Evaluation of D-TACE combined with endovascular brachytherapy for HCC with MPVTT - Huang, Wei; Gong, Ju; Wang, Qingbing; Wang, Ziyin; Liu, Qin; Liu, Jingjing; Gu, Junwei; Ding, Xiaoyi; Wu, Zhiyuan (Frontiers in Oncology, 2022)
Background Hepatocellular carcinoma (HCC) patients with main portal vein tumor thrombus (MPVTT) may be able to have TACE through stent implantation into the portal vein with thrombosis to recover portal blood flow. Purpose The goal of this study was to compare clinical results of conventional transcatheter arterial chemoembolization (C-TACE) and doxorubicin-eluting bead transcatheter arterial chemoembolization (D-TACE) combined with endovascular brachytherapy in HCC patients with MPVTT. Methods This study was a retrospective controlled study with follow-up dates spanning from Mar 2015 to Feb 2020. Patients with both HCC and MPVTT were divided into two groups. Portal vein stents with iodine-125 seed strands were implanted first; then, C-TACE or D-TACE was administered to all patients. Objective response rates were assessed. Results A total of 26 patients were enrolled, with 13 in each group. During follow-up, the portal stent patency times were 112.3 ± 98.2 days in the C-TACE group and 101.7 ± 90.4 days in the D-TACE group. The time to disease progression was 42 days in the C-TACE group and 120 days in the D-TACE group (p=0.03). The overall survival time from the first intervention procedure was 216 days in the C-TACE group and 239 days in the D-TACE group (p=0.047). The D-TACE group was superior to the C-TACE group in terms of progression-free survival (PFS) and overall survival (OS) times. Conclusion Endovascular implantation of brachytherapy combined with TACE is safe and effective in HCC patients with MPVTT. This combination therapy may be helpful for survival benefits to patients with stage BCLC-C HCC.